2018
DOI: 10.1007/s00704-018-2459-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal structure of thermal inversions in Łeba (Poland)

Abstract: This study presents the detailed characteristics of thermal inversions based on a 10-year aerological measurement series (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) conducted in Łeba (Poland). The analyses included surface-based inversions (SBIs) and elevated inversions (ELIs) in the atmospheric layer up to 3000 m. In the case of SBIs, this layer extended directly from the ground level to an altitude above which the air temperature decreases with altitude, whereas for ELIs, which have a base a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 46 publications
5
28
1
Order By: Relevance
“…() and Czarnecka et al . () indicated similar temporal variations in the inversion depth and strength as well as EI base height. Also, Joly and Richard () concluded that their results obtained on the basis of the observational data for the Jura Mountains are consistent with those obtained in our previous studies on SBI parameters (Palarz et al ., ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…() and Czarnecka et al . () indicated similar temporal variations in the inversion depth and strength as well as EI base height. Also, Joly and Richard () concluded that their results obtained on the basis of the observational data for the Jura Mountains are consistent with those obtained in our previous studies on SBI parameters (Palarz et al ., ).…”
Section: Discussionsupporting
confidence: 86%
“…On the macro‐scale, the variations identified for EI frequency are generally not accompanied by changes in other EI parameters. This does not preclude, however, the validity of the trends observed on a more local scale (Stryhal et al ., ; Czarnecka et al ., ). For example, Stryhal et al .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations